Percutaneous endoscopic gastrostomy: a safe and effective bridge for enteral nutrition in neurological or non-neurological conditions - (:unkn) unknown (My University, 2004)
Percutaneous endoscopic gastrostomy (PEG) is one of the most commonly used methods for nutritional support in patients who are unable to take food orally. Traditional surgical gastrostomy, percutaneous radiologic gastrostomy, and laparoscopic gastrostomy are the alternatives. The most common indication is neurogenic dysphagia followed by obstructive causes such as head and neck tumors. Ethically justified and clinically comprehensive guidelines should be followed during the decision-making process for PEG tube placement. A limited life expectancy; technical difficulties, such as the inability to bring the anterior gastric wall in apposition to the abdominal wall; or pharyngeal/esophageal obstruction, which compromise tube insertion, peritonitis, and uncorrectable coagulopathy are absolute contraindications. The "pull method" is the first described and still the most performed technique of PEG tube placement. The procedure is simple, safe, and effective and fulfills all requirements to provide an ideal route for nutritional support. This article summarizes the reported experience on PEG in the current literature and discusses its utility in patients with neurological conditions.
Keywords: Humans; Nervous System Diseases; Endoscopy, Digestive System; Enteral Nutrition; Gastrostomy; Deglutition Disorders; Intubation, Gastrointestinal